2013
DOI: 10.3892/or.2013.2327
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in head and neck cancer: The role of the secretory leukocyte protease inhibitor

Abstract: Abstract. We previously showed that secretory leukocyte protease inhibitor (SLPI) gene and protein expression is significantly lower in metastatic versus non-metastatic head and neck squamous cell carcinoma (HNSCC). However, we did not assess the human papillomavirus (HPV) status of these cases. Since SLPI plays a role in HIV and herpes simplex virus (HSV) infections, we hypothesized that SLPI may be involved in HPV-infected HNSCC. In HNSCC tissue (n=54), HPV DNA was determined and correlated with SLPI express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 30 publications
7
46
4
1
Order By: Relevance
“…As shown previously (1)(2)(3), both the secretory leucocyte protease inhibitor (SLPI; an antiproteinase) and the membrane bound receptor Annexin A2 (AnxA2) showed higher expression levels in smokers in comparison to non-smokers. However, SLPI showed a clear surplus compared to AnxA2 in smokers vs. non-smokers whereas AnxA2 vs. SLPI showed a significant surplus in cases tested HPV-positive when compared to HPV-negative cases (1)(2)(3). Previous ex vivo data showed that SLPI expression in clinically healthy mucosa of the lower turbinates can be increased by incubation with nicotine (2).…”
Section: Introductionsupporting
confidence: 63%
“…As shown previously (1)(2)(3), both the secretory leucocyte protease inhibitor (SLPI; an antiproteinase) and the membrane bound receptor Annexin A2 (AnxA2) showed higher expression levels in smokers in comparison to non-smokers. However, SLPI showed a clear surplus compared to AnxA2 in smokers vs. non-smokers whereas AnxA2 vs. SLPI showed a significant surplus in cases tested HPV-positive when compared to HPV-negative cases (1)(2)(3). Previous ex vivo data showed that SLPI expression in clinically healthy mucosa of the lower turbinates can be increased by incubation with nicotine (2).…”
Section: Introductionsupporting
confidence: 63%
“…We have previously provided evidence that HNSCC patients with lower SLPI levels are more likely to have HPV-positive cancers, demonstrating a correlation between reduced SLPI and increased HPV infection in vivo (Cordes et al, 2011;Hoffmann et al, 2013). With this observation in mind, we utilized the HSV-mediated reduced SLPI environment to examine the effect of HPV16 uptake and infection in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned in vitro data, a strong inverse correlation exists between the expression of the innate immune protein SLPI, and the HPV status and degree of metastasis of HNSCC in vivo (Cordes et al, 2011;Hoffmann et al, 2013). Specifically, it was found that higher SLPI levels were correlated with lower HPV expression in vivo.…”
Section: Introductionmentioning
confidence: 97%
“…It is found in various bodily secretions, but is present in particularly high concentrations in the saliva [8]. The role of salivary SLPI in reducing transmission of HIV in the oral cavity has been well studied [9, 10], and there is growing evidence that SLPI may protect against oral HPV infection [11, 12]. Results from tumor studies suggest that SLPI may be associated with HNC carcinogenesis [7], metastasis [11, 13], and prognosis [14], although the exact mechanisms by which SLPI protects against HNC development and progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The role of salivary SLPI in reducing transmission of HIV in the oral cavity has been well studied [9, 10], and there is growing evidence that SLPI may protect against oral HPV infection [11, 12]. Results from tumor studies suggest that SLPI may be associated with HNC carcinogenesis [7], metastasis [11, 13], and prognosis [14], although the exact mechanisms by which SLPI protects against HNC development and progression remain unclear. SLPI is believed to protect mucosal surfaces against proteolysis and epithelial tissue damage [15] by inhibiting neutrophil elastase, a serine protease produced by tumor and inflammatory cells that is known to induce tumor cell proliferation [16].…”
Section: Introductionmentioning
confidence: 99%